Feiras negras em São Paulo: um estudo sobre o desenvolvimento e a dimensão da consciência política - Santos, Adriano Alves dos Reis (2023)
This study proposes to understand the importance of collective spaces for the development of afroentrepreneurs and Brazilian afroentrepreneurship. To this end, we followed the training of 100 afroentrepreneurs, who participated in black fairs in five cities: Americana, Campinas, Piracicaba, Rio Claro and Santos. The research was carried out between the months of July and September 2022. This work aimed to analyze the development and construction of spaces of political awareness, considering racial issues in Brazil. We use as main elements the theory of political consciousness and contributions on racism and afroentrepreneurship. Three survey questionnaires were administered to Afroentrepreneurs and an interview with each fair leader in each city